Method for repairing steel plate with seriously rusted local part
By applying a multi-layer repair system on locally corroded steel plates, the problems of safety risks and insufficient bearing capacity in the existing technology are solved, and the effect of significantly improving the corrosion resistance and bearing capacity of the steel plates is achieved.
Patent Information
- Application Number
- CN202411662903.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The prior art poses safety risks when repairing locally corroded steel plates, and the repaired steel plates lack the bearing capacity and corrosion resistance, making it difficult to meet the safe operation needs of steel structure facilities.
A multi-layer repair system is adopted, including zinc-rich primer layer, non-woven reinforced high barrier layer, fiber grille reinforced bearing layer and wear-resistant and anti-corrosion cover layer. The corrosion resistance and load bearing capacity of the steel plate are significantly improved through layered repair.
It significantly improves the corrosion resistance and load-bearing capacity of locally corroded steel plates, enhances the wear resistance and durability of the steel plate repair location, extends the service life of the steel plate after repair, and reduces construction safety risks.
Smart Images

Figure BDA0005143900250000061 
Figure BDA0005143900250000071 
Figure BDA0005143900250000072
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of maintenance and protection of steel structures, and more specifically, to a method for repairing a locally severely corroded steel plate. Background Art
[0002] In industries such as chemical, petroleum and ports, steel structure platforms are often used as working surfaces. However, steel structure systems are susceptible to corrosion in high humidity and corrosive environments, resulting in reduced safety, usability and durability. Due to the accumulation of corrosive media or defects in anti-corrosion coatings, steel plates on steel structure platforms or stairs often suffer from local severe damage, and the presence of local corrosion will seriously reduce the bearing capacity and ductility of steel plates in actual projects, causing the overall performance of the steel structure system to continue to deteriorate, seriously threatening the safe operation of steel structure facilities. Therefore, the repair of locally corroded steel plates becomes particularly important. The repair process of steel structure steel plates should be free of safety risks, and the repaired steel plates should have good bearing capacity and corrosion resistance, and can work safely and reliably.
[0003] Existing repair methods for locally corroded steel structures include grouting reinforcement, welding ribs or steel plates, grouting clamp reinforcement, internal filling concrete reinforcement, fiber (FRP) sandwich grouting reinforcement, carbon fiber (CFRP) reinforcement and laser cladding technology.
[0004] With regard to the above-mentioned related technologies, the inventors found that for the repair of the steel plate structure of the floor, due to the large fluidity of the slurry, grouting and grouting clamp reinforcement methods are not applicable; welding ribs or steel plate pasting methods cannot solve the problem of steel plate corrosion, and there are safety risks in the welding process, and it is also easy to cause new damage to the steel plate; the internal filling concrete reinforcement method will significantly increase the thickness of the steel plate, and when the concrete is too thin, its tensile and flexural strengths cannot meet the requirements, and it is not suitable for repairing the steel plate; the fiber sandwich grouting and carbon fiber reinforcement methods and laser cladding technology are all relatively expensive, and the process is complicated, and are not suitable for large-scale application. Summary of the invention
[0005] In order to improve the effect of repairing a steel plate that is severely corroded locally, the present application provides a method for repairing a steel plate that is severely corroded locally.
[0006] In a first aspect, the present application provides a method for repairing a locally severely corroded steel plate, using the following technical solution: A method for repairing a locally severely corroded steel plate, comprising the following steps: S1. Clean the rust on the surface of the steel plate and extend it around the edge of the damaged part to divide the area to be repaired; S2. Apply water-based EAU zinc-rich primer to the area to be repaired, and form a zinc-rich primer layer after drying and curing; S3. Use non-woven fabric to soak the water-based EAU high barrier midcoat, stick it on the surface of the zinc-rich primer layer, and form a non-woven fabric reinforced high barrier layer after drying and curing; S4. Lay glass fiber civil grid, build enclosure around the damaged part, and then pour water-based EAU high barrier mid-coat, which will form a fiber grid reinforced bearing layer after drying and curing; S5. Finally, apply water-based EAU wear-resistant and anti-corrosion topcoat on the surface of the fiber grid reinforced bearing layer. After drying and curing, a wear-resistant and anti-corrosion cover layer is formed to form a multi-layer repair system, and the repair is completed.
[0007] By adopting the above technical scheme, a multi-layer repair system structure having a zinc-rich primer layer, a non-woven fabric reinforced high barrier layer, a fiber grid reinforced bearing layer and a wear-resistant and anti-corrosion covering layer is formed from bottom to top on the surface of the locally severely corroded steel plate. Through the layered repair method, the corrosion resistance and bearing capacity of the locally corroded steel plate are significantly improved. The wear-resistant and anti-corrosion covering layer formed on the top layer improves the durability and wear resistance of the repaired part of the steel plate.
[0008] The coatings made from water-based EAU materials use water as solvent, do not contain heavy metal ions and other harmful substances, and their low volatile organic compound (VOC) content makes the construction more environmentally friendly. At the same time, water as a solvent also reduces safety risks during the construction process.
[0009] As a reinforcing material, non-woven fabric can significantly enhance the structural strength of water-based EAU high barrier mid-coat, making the formed non-woven fabric reinforced high barrier layer have excellent bearing capacity, more durable and stable. At the same time, non-woven fabric reinforced water-based EAU high barrier mid-coat further improves the barrier performance of the mid-coat, effectively blocking moisture and corrosive media from penetrating the coating, providing good protection for the substrate structure, thereby protecting the steel plate from further corrosion.
[0010] The fiberglass civil grid has high strength and durability, which significantly improves the tensile strength and tear strength of the water-based EAU high barrier midcoat. The three-dimensional structure of the fiberglass civil grid can provide better support and fixation, making the bonding between the midcoat and the substrate structure stronger. It effectively enhances the overall bearing capacity of the steel plate and reduces the risk of further deformation or damage to the steel plate.
[0011] When micro cracks appear in the multi-layer repair system, both non-woven fabrics and fiberglass civil grids can bridge these cracks and prevent them from expanding into larger damage.
[0012] Optionally, before applying the water-based EAU zinc-rich primer to the area to be repaired in step S2, the following pretreatment is performed: applying the water-based EAU rust-resistant primer to the area to be repaired, and forming a rust-resistant primer layer after drying and curing.
[0013] By adopting the above technical solution, the repair method of the present application can be used with rust, without the need for sandblasting to remove rust. This is because when the anti-rust primer prepared with water-based EAU material is coated on the surface of the steel plate, the active ingredients such as the rust converter inside can penetrate into the rust layer, react chemically with the rust layer on the surface of the steel plate, and convert the oxidized rust on the surface of the steel plate into a solid complex, thereby fixing the rust and preventing the further spread of rust. Compared with the traditional sandblasting rust removal method, the water-based EAU material does not produce a large amount of wastewater, waste residue and dust during construction, which is beneficial to protecting the health of construction workers and the environment.
[0014] When the steel plate is rusted and cannot be derusted, the repair method of the present application can exert a significant repair effect and establish a stable rust-resistant primer layer for the multi-layer repair system.
[0015] Optionally, the raw materials of the water-based EAU anti-rust primer include a composite emulsion and a curing component in parts by weight; In parts by weight, the composite emulsion includes 90-110 parts of aqueous EAU composite resin emulsion; The curing components include 12-16 parts of curing agent, 0.1-0.3 parts of wetting agent, 0.2-0.5 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.6-1.2 parts of film-forming aid, 12.5-17.5 parts of aminotrimethylenephosphonic acid, 11-16 parts of zinc phosphate, 5-9 parts of aluminum tripolyphosphate and 25-35 parts of water.
[0016] By adopting the above technical scheme, aminotrimethylenephosphonic acid has good dispersibility and sustained-release properties, can dissolve oxides on the metal surface, and form strong and stable complexes with various metal ions such as iron, copper, aluminum, zinc, etc., thereby effectively removing dirt and oxides on the metal surface and improving the smoothness and corrosion resistance of the metal surface.
[0017] Zinc phosphate can react with Fe on the metal surface 3+ It forms a firm complex and deposits on the metal surface to form a dense protective film, which has good corrosion inhibition and shielding effects, effectively inhibits the anodic reaction on the metal surface, and prevents further oxidation and corrosion of the locally severely corroded steel plate. It can also form a corrosion-inhibiting complex with the hydroxyl, carboxyl and other functional groups in the anti-rust primer, so that the water-based EAU anti-rust primer and the steel plate substrate form a chemical bond, which improves the adhesion and impermeability of the coating.
[0018] After zinc phosphate and aminotrimethylenephosphonic acid are compounded, the primer formed is easy to mix evenly, and is not prone to defects such as sagging and brush marks during coating. Both of them are non-toxic or low-toxic substances, and the primer formed after compounding meets environmental protection requirements.
[0019] Optionally, the raw materials of the water-based EAU zinc-rich primer include a composite emulsion, a curing component and a powder component; in parts by weight, the composite emulsion includes 90-110 parts of water-based EAU composite resin emulsion; The curing component includes 12-16 parts of curing agent, 0.1-0.3 parts of wetting agent, 0.3-0.6 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.6-1 parts of film-forming aid and 25-35 parts of water; The powder components include 59-67 parts of zinc powder and 3-5 parts of nano calcium carbonate.
[0020] By adopting the above technical solution, zinc powder is a chemically active pigment, the electrode potential of zinc is -0.7628V, and the electrode potential of iron is -0.409V. Therefore, zinc can act as a sacrificial anode on the surface of steel, protecting the surface of the steel plate and preventing the steel plate substrate from further corrosion. At the same time, the corrosion product of zinc powder can fill the pores between the primer and the substrate, sealing the damaged parts of the steel plate substrate.
[0021] The protective mechanism of the sacrificial anode and the physical bonding between the zinc powder and the substrate significantly enhance the bonding force between the zinc-rich primer layer and the steel plate substrate, thereby improving the repair effect of the repair method of the present application.
[0022] The addition of nano calcium carbonate can fill the microstructure of the coating, reduce pores and defects, significantly improve the density of the coating, and improve the overall performance of the zinc-rich primer layer.
[0023] Optionally, the raw materials of the water-based EAU high-barrier mid-coat include a composite emulsion, a curing component and a reinforcing powder; in parts by weight, the composite emulsion includes 80-100 parts of a water-based EAU composite resin emulsion; The curing component comprises 11.2-15.7 parts of curing agent, 0.1-0.3 parts of wetting agent, 0.2-0.5 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.6-1.2 parts of film-forming aid, 0.3-0.6 parts of anti-settling agent, 0.3-0.6 parts of cellulose ether and 32-38 parts of water; The reinforcing powder comprises 15.6-22.4 parts of slag powder, 3-7 parts of steel slag powder and 1.2-1.9 parts of sodium silicate.
[0024] By adopting the above technical solution, the inorganic micro-powder mixture formed by ultra-fine slag powder and ultra-fine steel slag powder can react with alkaline sodium silicate to form an alkali-activated gel material. This alkali-activated gel material has a certain strength and can form a good bond with the fiber-reinforced grid under the action of the composite emulsion to form a composite material load-bearing layer, effectively improving the bonding between the layers of the multi-layer repair system, so that the bearing capacity of the multi-layer repair system meets the required standard.
[0025] Optionally, the raw materials of the water-based EAU wear-resistant and anti-corrosion topcoat include a composite emulsion, a curing component and a reinforcing powder; In parts by weight, the composite emulsion includes 80-100 parts of aqueous EAU composite resin emulsion; The curing component includes 11-14 parts of curing agent, 0.2-0.4 parts of wetting agent, 0.2-0.4 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.5-0.8 parts of film-forming aid, 0.2-0.4 parts of leveling agent, 5-8 parts of water-based color paste and 25-32 parts of water; The reinforcing powder comprises 2.5-5.5 parts of silicon carbide and 3-7 parts of nano silicon dioxide.
[0026] By adopting the above technical scheme, both silicon carbide and nano-silicon dioxide have high hardness and strength. After mixing, they can give full play to the advantages of silicon carbide and nano-silicon dioxide in wear resistance, so that the wear-resistant and anti-corrosion overlay layer formed can withstand greater external forces and pressures and have higher wear resistance.
[0027] Optionally, the curing agent is any one of a water-based polyurea resin or a polyisocyanate curing agent or a combination of both.
[0028] Optionally, the area to be repaired is within an area extending 10-50 cm in all directions along the edge of the damaged part.
[0029] Optionally, the thickness of the non-woven fabric reinforced high barrier layer is 0.5-1 mm, and the thickness of the fiber grid reinforced bearing layer is 3-5 mm.
[0030] By adopting the above technical solution, the bearing capacity of the multi-layer repair system can be adjusted by designing the thickness of the non-woven fabric reinforced high barrier layer, designing the thickness of the glass fiber civil grid and adjusting the thickness of the fiber grid reinforced bearing layer.
[0031] In summary, this application has the following beneficial effects: 1. The repair method of the present application forms a multi-layer repair system structure around the locally severely corroded steel plate through a layered repair method, which significantly improves the corrosion resistance and load-bearing capacity of the corroded steel plate. The outermost wear-resistant and anti-corrosion surface layer enhances the wear resistance and durability of the steel plate repair position, further extending the service life of the repaired steel plate.
[0032] 2. Non-woven fabric reinforced water-based EAU high barrier mid-coat and 3D fabric reinforced water-based EAU high barrier mid-coat effectively enhance the overall bearing capacity of the steel plate and reduce the risk of further deformation or damage of the steel plate.
[0033] 3. The zinc phosphate particles in the water-based EAU anti-rust primer are relatively fine, and by reacting with the rust layer and other components in the primer, a dense phosphate protective film is formed on the surface of the steel plate, which significantly improves the adhesion and smoothness between the primer layer and the steel plate substrate; while the zinc powder particles of the water-based EAU zinc-rich primer are relatively large, and through the protection mechanism of the sacrificial anode, it effectively inhibits and shields the locally severely rusted steel plates. The increase of the anti-rust primer layer makes the two primer layers complement each other, so that the repair effect of the repair method of the present application is significantly improved when repairing steel plates that are severely corroded to the point where rust removal is impossible.
[0034] 4. The repair method of this application uses paint made of water-based EAU materials, which can be used in rust-resistant operations without sandblasting and rust removal. The construction is safe, there is no fire risk, and it meets the requirements of environmental protection and sustainable development. DETAILED DESCRIPTION
[0035] The following examples and comparative examples further illustrate the present application in detail.
[0036] raw material Unless otherwise specified, the raw materials used in the examples and comparative examples of this application are all commercially available products, specifically: Polytetramethylene glycol, selected from Deyitai New Materials, DYT-005; Toluene diisocyanate, selected from Shanghai Yuanye Biotechnology Co., Ltd., W10121; Dibutyltin dilaurate, selected from Shanghai Yuanye Biotechnology Co., Ltd., W10608; Hydroxyethyl acrylate, selected from Jingtai Chemical, A264959; Benzoyl peroxide, selected from West Asia Chemical, A65330; Tripropylene glycol diacrylate, selected from Youming Chemical, EM223TF; Bisphenol A epoxy resin, selected from Senqiang Environmental Technology, E-44; Water-based polyurea resin curing agent, selected from Jinwanli, J-6736; Polyisocyanate curing agent, selected from Shiquanxing, F-38; Wetting agent, selected from Evonik Digo, Twin4100; Dispersant, selected from BYK, BYK163; Defoaming agent, selected from BYKA, BYKA500; Film-forming aid, selected from Runtai Chemical, 23812; Anti-settling agent, selected from Zhonglian Federation, K-288; Cellulose ether, which is carboxymethyl cellulose, selected from Jianyang Xinghua, XH-666; Leveling agent, selected from BYK, BYK333; Water-based color paste, selected from AStrong, WVW107; Aminotrimethylenephosphonic acid, selected from Haoyao New Materials, HY565; Zinc phosphate, selected from Lehuan, lh-lsx, with a particle size of 800 mesh; Zinc powder, purity ≥99.5%, particle size 200 mesh; Nano-silicon dioxide, average particle size is 20nm; Fiberglass civil grid, selected from Shandong Lianxiang Engineering Materials Co., Ltd.; Nano calcium carbonate, which is modified calcium carbonate, was selected from Hangzhou Jikang New Materials Co., Ltd., SS-CAC50; Slag powder, specific surface area ≥ 600m 2 / Kg; Steel slag powder, specific surface area ≥ 600m 2 / Kg.
[0037] Preparation of water-based EAU composite resin emulsion The water-based EAU composite resin emulsion is selected from Suzhou Dacheng Environmental Protection New Materials Co., Ltd., and the raw materials include 40g of polytetramethylene ether glycol, 10g of toluene diisocyanate, 0.5g of dibutyltin dilaurate, 8g of dimethyl carbonate, 22.6g of hydroxyethyl acrylate, 7g of benzoyl peroxide, 14g of tripropylene glycol diacrylate and 45g of bisphenol A epoxy resin; the preparation method of the above-mentioned water-based EAU composite resin emulsion comprises the following steps: In a nitrogen atmosphere, polytetramethylene glycol and toluene diisocyanate were added to a reaction vessel, heated and stirred at 80°C, dibutyltin dilaurate and dimethyl carbonate were added, and the reaction was continued with stirring for 3.5 hours, and then hydroxyethyl acrylate was added for end-capping, and then poured into 150 mL of deionized water and stirred to obtain a polyurethane acrylate emulsion; The bisphenol A epoxy resin and the polyurethane acrylate emulsion are mixed and stirred, and then benzoyl peroxide and tripropylene glycol diacrylate are added. The mixture is stirred and reacted at 150° C. and 350 r / min for 2.5 hours, and then cooled and discharged to obtain the product.
[0038] Preparation Example 1.1-1.3 of Water-Based EAU Rust-Reducing Primer Preparation Example 1.1 The raw materials and dosage of the water-based EAU anti-rust primer are shown in Table 1, wherein the curing agent is a water-based polyurea resin and a polyisocyanate curing agent in a mass ratio of 1:1, and the water is deionized water.
[0039] Table 1 The preparation method of the above-mentioned water-based EAU anti-rust primer comprises the following steps: S1. The curing agent, wetting agent, dispersant, defoamer, film-forming agent, aminotrimethylenephosphonic acid, zinc phosphate, aluminum tripolyphosphate and water are mixed and stirred to form a curing component; S2. Evenly mix the water-based EAU composite resin emulsion and the curing component to obtain.
[0040] Preparation Example 1.2-1.3 The water-based EAU anti-rust primer is different from Preparation Example 1.1 in that the raw materials and amounts are shown in Table 1, and the other steps are the same as Preparation Example 1.1.
[0041] Preparation Example 2.1-2.3 of Waterborne EAU Zinc-Rich Primer Preparation Example 2.1 The raw materials and dosage of the water-based EAU zinc-rich primer are shown in Table 2, wherein the curing agent is a water-based polyurea resin and a polyisocyanate curing agent in a mass ratio of 1:1, and the water is deionized water.
[0042] Table 2 The preparation method of the above-mentioned water-based EAU zinc-rich primer comprises the following steps: S1. Mix the curing agent, wetting agent, dispersant, defoamer, film-forming agent and water to form a curing component; S2. The zinc powder and nano-calcium carbonate are mixed to form a powder; S3. Evenly mix the water-based EAU composite resin emulsion, the curing component and the powder to obtain.
[0043] Preparation Example 2.2-2.3 The difference between the water-based EAU zinc-rich primer and Preparation Example 2.1 is that the raw materials and amounts are shown in Table 2, and the other steps are the same as Preparation Example 2.1.
[0044] Preparation Example 3.1-3.3 of Water-Based EAU High Barrier Midcoat Preparation Example 3.1 The raw materials and dosage of water-based EAU high barrier mid-coat are shown in Table 3, wherein the curing agent is a polyisocyanate curing agent and the water is deionized water.
[0045] Table 3 The preparation method of the above-mentioned water-based EAU high barrier mid-coat comprises the following steps: S1. The curing agent, wetting agent, dispersant, defoaming agent, film-forming aid, anti-settling agent, cellulose ether and water are mixed uniformly to form a curing component; S2. Mixing slag powder, steel slag powder and sodium silicate to form a reinforcing powder; S3. Evenly mix the water-based EAU composite resin emulsion, the curing component and the reinforcing powder to obtain.
[0046] Preparation Examples 3.2-3.3 The difference between the water-based EAU high barrier mid-coat and Preparation Example 3.1 is that the raw materials and amounts are shown in Table 3, and the other steps are the same as Preparation Example 3.1.
[0047] Preparation Example 4.1-4.3 of water-based EAU wear-resistant and anti-corrosion topcoat Preparation Example 4.1 Water-based EAU wear-resistant and anti-corrosion topcoat, the raw materials and dosage are shown in Table 4, where the curing agent is water-based polyurea resin and the water is deionized water Table 4 The preparation method of the above-mentioned water-based EAU wear-resistant and anti-corrosion topcoat comprises the following steps: S1. Mix the curing agent, wetting agent, dispersant, defoamer, film-forming aid, leveling agent, water-based color paste and water to form a curing component; S2. Mixing silicon carbide and nano-silicon dioxide to form a reinforcing powder; S3. Evenly mix the water-based EAU composite resin emulsion, the curing component and the reinforcing powder to obtain.
[0048] Preparation Examples 4.2-4.3 The water-based EAU wear-resistant and anti-corrosion topcoat is different from Preparation Example 4.1 in that the raw materials and amounts are shown in Table 4, and the other steps are the same as Preparation Example 4.1. Example
[0049] Example 1 A method for repairing a locally severely corroded steel plate comprises the following steps: S1. Clean the rust on the surface of the steel plate and extend 35cm around the edge of the damaged part to form the area to be repaired; S2. Apply the water-based EAU rust-killing primer obtained in Preparation Example 1.1 to the area to be repaired, convert the oxide rust on the surface of the steel plate into a solid complex, and form a rust-killing primer layer after drying and curing. The thickness of the rust-killing primer layer is 30 μm; S3. Apply the water-based zinc-rich primer EAU obtained in Preparation Example 2.1 on the surface of the rust primer layer, and form a zinc-rich primer layer after drying and curing, the thickness of the zinc-rich primer layer is 50μm; S4. A non-woven fabric is impregnated with a water-based EAU high barrier midcoat and pasted on the surface of the zinc-rich primer layer. After drying and curing, a non-woven fabric reinforced high barrier layer is formed. The thickness of the non-woven fabric reinforced high barrier layer is 0.65 mm. The water-based EAU high barrier midcoat is obtained by Preparation Example 3.1; S5. Lay glass fiber civil grid on the non-woven fabric reinforced high barrier layer, build enclosures around the damaged area, and then pour water-based EAU high barrier mid-coat on the glass fiber civil grid. After drying and curing, a fiber grid reinforced bearing layer is formed. The thickness of the fiber grid reinforced bearing layer is 3.5 mm. S6. Finally, the surface of the fiber grid reinforced bearing layer is coated with the water-based EAU wear-resistant and anti-corrosion topcoat obtained in Preparation Example 4.1. After drying and curing, a wear-resistant and anti-corrosion overcoat is formed to form a multi-layer repair system, and the repair is completed. The thickness of the wear-resistant and anti-corrosion overcoat is 60 μm.
[0050] Example 2 A method for repairing a locally severely corroded steel plate comprises the following steps: S1. Clean the rust on the surface of the steel plate and extend 10cm around the edge of the damaged part to form the area to be repaired; S2. Apply the water-based EAU rust-killing primer obtained in Preparation Example 1.1 to the area to be repaired, convert the oxide rust on the surface of the steel plate into a solid complex, and form a rust-killing primer layer after drying and curing. The thickness of the rust-killing primer layer is 30 μm; S3. Apply the water-based zinc-rich primer EAU obtained in Preparation Example 2.1 on the surface of the rust primer layer, and form a zinc-rich primer layer after drying and curing, the thickness of the zinc-rich primer layer is 50μm; S4. A non-woven fabric is impregnated with a water-based EAU high barrier midcoat and pasted on the surface of the zinc-rich primer layer. After drying and curing, a non-woven fabric reinforced high barrier layer is formed. The thickness of the non-woven fabric reinforced high barrier layer is 1 mm. The water-based EAU high barrier midcoat is obtained by Preparation Example 3.1; S5. Lay glass fiber civil grid on the non-woven fabric reinforced high barrier layer, build enclosures around the damaged area, and then pour water-based EAU high barrier mid-coat on the glass fiber civil grid. After drying and curing, a fiber grid reinforced bearing layer is formed. The thickness of the fiber grid reinforced bearing layer is 3 mm. S6. Finally, the surface of the fiber grid reinforced bearing layer is coated with the water-based EAU wear-resistant and anti-corrosion topcoat obtained in Preparation Example 4.1. After drying and curing, a wear-resistant and anti-corrosion overcoat is formed to form a multi-layer repair system, and the repair is completed. The thickness of the wear-resistant and anti-corrosion overcoat is 60 μm.
[0051] Example 3 A method for repairing a locally severely corroded steel plate comprises the following steps: S1. Clean the rust on the surface of the steel plate and extend 50cm around the edge of the damaged part to form the area to be repaired; S2. Apply the water-based EAU rust-killing primer obtained in Preparation Example 1.1 to the area to be repaired, convert the oxide rust on the surface of the steel plate into a solid complex, and form a rust-killing primer layer after drying and curing. The thickness of the rust-killing primer layer is 30 μm; S3. Apply the water-based zinc-rich primer EAU obtained in Preparation Example 2.1 on the surface of the rust primer layer, and form a zinc-rich primer layer after drying and curing, the thickness of the zinc-rich primer layer is 50μm; S4. A non-woven fabric is impregnated with a water-based EAU high barrier midcoat and pasted on the surface of the zinc-rich primer layer. After drying and curing, a non-woven fabric reinforced high barrier layer is formed. The thickness of the non-woven fabric reinforced high barrier layer is 0.5 mm. The water-based EAU high barrier midcoat is obtained by Preparation Example 3.1; S5. Lay glass fiber civil grid on the non-woven fabric reinforced high barrier layer, build enclosures around the damaged area, and then pour water-based EAU high barrier mid-coat on the glass fiber civil grid. After drying and curing, a fiber grid reinforced bearing layer is formed. The thickness of the fiber grid reinforced bearing layer is 5 mm. S6. Finally, the surface of the fiber grid reinforced bearing layer is coated with the water-based EAU wear-resistant and anti-corrosion topcoat obtained in Preparation Example 4.1. After drying and curing, a wear-resistant and anti-corrosion overcoat is formed to form a multi-layer repair system, and the repair is completed. The thickness of the wear-resistant and anti-corrosion overcoat is 60 μm.
[0052] Example 4 A method for repairing a locally severely corroded steel plate, which differs from Example 1 in that no water-based EAU anti-rust primer is applied to the area to be repaired, and no anti-rust primer layer exists in the repaired structure of the steel plate, and specifically comprises the following steps: S1. Clean the rust on the surface of the steel plate and extend 35cm around the edge of the damaged part to form the area to be repaired; S2. Apply the water-based EAU zinc-rich primer obtained in Preparation Example 2.1 to the area to be repaired, and form a zinc-rich primer layer after drying and curing, and the thickness of the zinc-rich primer layer is 50 μm; S3. A non-woven fabric is impregnated with a water-based EAU high barrier midcoat and pasted on the surface of the zinc-rich primer layer. After drying and curing, a non-woven fabric reinforced high barrier layer is formed. The thickness of the non-woven fabric reinforced high barrier layer is 0.65 mm. The water-based EAU high barrier midcoat is obtained by Preparation Example 3.1; S4. Lay glass fiber civil grid on the non-woven fabric reinforced high barrier layer, build enclosures around the damaged area, and then pour water-based EAU high barrier mid-coat on the glass fiber civil grid. After drying and curing, a fiber grid reinforced bearing layer is formed. The thickness of the fiber grid reinforced bearing layer is 3.5 mm. S5. Finally, the surface of the fiber grid reinforced bearing layer is coated with the water-based EAU wear-resistant and anti-corrosion topcoat obtained in Preparation Example 4.1. After drying and curing, a wear-resistant and anti-corrosion overcoat is formed to form a multi-layer repair system, and the repair is completed. The thickness of the wear-resistant and anti-corrosion overcoat is 60 μm.
[0053] Comparative Example Comparative Example 1 A method for repairing a locally severely corroded steel plate, which differs from Example 4 in that no non-woven fabric is used for reinforcement, and no non-woven fabric reinforced high-barrier layer is provided in the repair structure, specifically comprising the following steps: S1. Clean the rust on the surface of the steel plate and extend 35cm around the edge of the damaged part to form the area to be repaired; S2. Apply the water-based EAU zinc-rich primer obtained in Preparation Example 2.1 to the area to be repaired, and form a zinc-rich primer layer after drying and curing, and the thickness of the zinc-rich primer layer is 50 μm; S3. Lay a glass fiber civil grid on the zinc-rich primer layer, fence around the damaged area, and then pour the water-based EAU high barrier midcoat obtained in Preparation Example 3.1 onto the glass fiber civil grid, and form a fiber grid reinforced bearing layer after drying and curing. The thickness of the fiber grid reinforced bearing layer is 4.5 mm; S4. Finally, the surface of the fiber grid reinforced bearing layer is coated with the water-based EAU wear-resistant and anti-corrosion topcoat obtained in Preparation Example 4.1. After drying and curing, a wear-resistant and anti-corrosion covering layer is formed to form a multi-layer repair system. The repair is completed, and the thickness of the wear-resistant and anti-corrosion covering layer is 60 μm.
[0054] Comparative Example 2 A method for repairing a locally severely corroded steel plate, which differs from Example 4 in that no glass fiber civil grid is used for reinforcement, and no fiber grid reinforcement bearing layer is provided in the repair structure, specifically comprising the following steps: S1. Clean the rust on the surface of the steel plate and extend 35cm around the edge of the damaged part to form the area to be repaired; S2. Apply the water-based EAU zinc-rich primer obtained in Preparation Example 2.1 to the area to be repaired, and form a zinc-rich primer layer after drying and curing, and the thickness of the zinc-rich primer layer is 50 μm; S3. A non-woven fabric is impregnated with a water-based EAU high barrier midcoat and pasted on the surface of the zinc-rich primer layer. After drying and curing, a non-woven fabric reinforced high barrier layer is formed. The thickness of the non-woven fabric reinforced high barrier layer is 0.65 mm. The water-based EAU high barrier midcoat is obtained by Preparation Example 3.1; S4. Finally, the water-based EAU wear-resistant and anti-corrosion topcoat obtained in Preparation Example 4.1 is applied on the surface of the non-woven fabric reinforced high barrier layer. After drying and curing, a wear-resistant and anti-corrosion covering layer is formed to form a multi-layer repair system. The repair is completed, and the thickness of the wear-resistant and anti-corrosion covering layer is 60 μm.
[0055] Comparative Example 3 A method for repairing a locally severely corroded steel plate, which differs from Example 4 in that non-woven fabric and glass fiber civil grid are not used for reinforcement, and specifically comprises the following steps: S1. Clean the rust on the surface of the steel plate and extend 35cm around the edge of the damaged part to form the area to be repaired; S2. Apply the water-based EAU zinc-rich primer obtained in Preparation Example 2.1 to the area to be repaired, and form a zinc-rich primer layer after drying and curing, and the thickness of the zinc-rich primer layer is 50 μm; S3. Apply the water-based EAU high-barrier midcoat obtained in Preparation Example 3.1 on the surface of the zinc-rich primer layer, and form a high-barrier reinforcement layer after drying and curing. The thickness of the high-barrier reinforcement layer is 0.65 mm; S4. Finally, the water-based EAU wear-resistant and anti-corrosion topcoat obtained in Preparation Example 4.1 is applied on the surface of the high-barrier reinforcement layer. After drying and curing, a wear-resistant and anti-corrosion covering layer is formed to form a multi-layer repair system. The repair is completed, and the thickness of the wear-resistant and anti-corrosion covering layer is 60 μm.
[0056] Comparative Example 4 A method for repairing a locally severely corroded steel plate, which differs from Example 4 in that no water-based EAU wear-resistant and anti-corrosion topcoat is applied to the area to be repaired, and no wear-resistant and anti-corrosion cover layer exists in the repair structure of the steel plate. The other steps are the same as Example 4.
[0057] Performance testing Seven steel plates with similar local severe rust and damage conditions were selected as test samples, and the eight steel plate samples were repaired using the repair methods of comparative examples 1-4 of embodiments 1-4, respectively. The following relevant performance test tests were performed on the repaired steel plates, and the test results are recorded in Table 5.
[0058] 1. Waterproofness: Refer to GB / T 16777-2008 "Test Methods for Building Waterproof Coatings", fix the repaired steel plate sample in the water-proof test device, apply a pressure of 0.4MPa to the sample surface, maintain for 2h, observe whether there is water penetration on the back of the steel plate sample, and record the test results in Table 5.
[0059] 2. Tensile adhesion strength: refer to CECS 343:2013 "Technical Code for Application of Anticorrosive Coatings for Steel Structures", and conduct tensile viscosity strength test on the surface of the repaired steel plate sample. The result ≥2MPa is qualified. Each group of tests is conducted 3 times, and the average value is taken as the final result and the test results are recorded in Table 5.
[0060] 3. Impact resistance: Refer to GB / T 1732-1993 "Determination of impact resistance of paint film", let a 1000g steel ball fall freely from a height of 100cm to impact the surface of the repaired steel plate sample, observe whether there are cracks, peeling and other phenomena on the surface of the steel plate sample, and record the test results in Table 5. The coating is qualified if there is no crack or peeling.
[0061] 4. Abrasion resistance test: Refer to GB / T 1768-2006 "Determination of abrasion resistance of paints and varnishes - Rotating rubber grinding wheel method", use an abrasion resistance tester, apply a load of 750g to the grinding wheel, set the speed to 500 rpm to wear the surface of the steel plate sample, record the average mass loss, and the result ≤0.03g is qualified.
[0062] 5. Liquid medium resistance test: refer to GB / T 9274-1988 "Determination of liquid medium resistance of coatings", immerse the steel plate samples in 30% hydrochloric acid solution for 48 hours, 30% sulfuric acid solution for 48 hours and 40% sodium hydroxide solution for 72 hours respectively, and observe whether there are bubbles, cracks, discoloration and other phenomena on the surface of the steel plate samples. The coating is qualified if there are no bubbles, cracks or discoloration.
[0063] Table 5 According to the performance test results in Table 5, it can be seen that the repair method of a locally severely corroded steel plate of the present application can effectively repair the locally severely corroded and damaged steel plate, and there is no safety risk in the repair process of the steel plate. The repaired steel plate has good load-bearing capacity and corrosion resistance and can work safely and reliably.
[0064] According to the performance test results of the steel plates repaired by the repair methods of Examples 1-4 and Comparative Examples 1-4, it can be seen that the non-woven fabric reinforced water-based EAU high barrier mid-coat and the glass fiber civil engineering grid reinforced water-based EAU high barrier mid-coat can effectively enhance the overall bearing capacity of the steel plate and reduce the risk of further deformation or damage of the steel plate. By designing the thickness of the glass fiber civil engineering grid, the bearing capacity of the multi-layer repair system can be adjusted.
[0065] The addition of the rust-resistant primer layer makes the advantages of the two primer layers, the rust-resistant primer layer and the zinc-rich primer layer, complement each other, so that the repairing effect of the repairing method of the present application is significantly improved when repairing steel plates that are severely corroded to the point where rust removal is impossible, and the repaired steel plates have excellent corrosion resistance and bearing capacity.
[0066] The wear-resistant and anti-corrosion cover layer formed by the water-based EAU wear-resistant and anti-corrosion topcoat can effectively improve the durability and wear resistance of the repaired parts of the steel plate and prevent the steel plate from further damage.
[0067] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for repairing a locally severely corroded steel plate, characterized in that: The following steps are involved: S1. Clean the rust on the surface of the steel plate and extend it around the edge of the damaged part to divide the area to be repaired; S2. Apply water-based EAU zinc-rich primer to the area to be repaired, and form a zinc-rich primer layer after drying and curing; S3. Use non-woven fabric to soak the water-based EAU high barrier midcoat, stick it on the surface of the zinc-rich primer layer, and form a non-woven fabric reinforced high barrier layer after drying and curing; S4. Lay glass fiber civil grid, build enclosure around the damaged part, and then pour water-based EAU high barrier mid-coat, which will form a fiber grid reinforced bearing layer after drying and curing; S5. Finally, apply water-based EAU wear-resistant and anti-corrosion topcoat on the surface of the fiber grid reinforced bearing layer. After drying and curing, a wear-resistant and anti-corrosion cover layer is formed to form a multi-layer repair system, and the repair is completed.
2. The method for repairing a locally severely corroded steel plate according to claim 1, characterized in that: In step S2, before applying the water-based EAU zinc-rich primer to the area to be repaired, the following pretreatment is performed: Apply water-based EAU anti-rust primer to the area to be repaired, and form an anti-rust primer layer after drying and curing.
3. The method for repairing a locally severely corroded steel plate according to claim 2, characterized in that: The raw materials of the water-based EAU anti-rust primer include a composite emulsion and a curing component; In parts by weight, the composite emulsion includes 90-110 parts of aqueous EAU composite resin emulsion; The curing components include 12-16 parts of curing agent, 0.1-0.3 parts of wetting agent, 0.2-0.5 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.6-1.2 parts of film-forming aid, 12.5-17.5 parts of aminotrimethylenephosphonic acid, 11-16 parts of zinc phosphate, 5-9 parts of aluminum tripolyphosphate and 25-35 parts of water.
4. The method for repairing a locally severely corroded steel plate according to claim 1, characterized in that: The raw materials of the water-based EAU zinc-rich primer include a composite emulsion, a curing component and a powder component; In parts by weight, the composite emulsion includes 90-110 parts of aqueous EAU composite resin emulsion; The curing component includes 12-16 parts of curing agent, 0.1-0.3 parts of wetting agent, 0.3-0.6 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.6-1 parts of film-forming aid and 25-35 parts of water; The powder components include 59-67 parts of zinc powder and 3-5 parts of nano calcium carbonate.
5. The method for repairing a locally severely corroded steel plate according to claim 1, characterized in that: The raw materials of the water-based EAU high barrier mid-coat include a composite emulsion, a curing component and a reinforcing powder; In parts by weight, the composite emulsion includes 80-100 parts of aqueous EAU composite resin emulsion; The curing component comprises 11.2-15.7 parts of curing agent, 0.1-0.3 parts of wetting agent, 0.2-0.5 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.6-1.2 parts of film-forming aid, 0.3-0.6 parts of anti-settling agent, 0.3-0.6 parts of cellulose ether and 32-38 parts of water; The reinforcing powder comprises 15.6-22.4 parts of slag powder, 3-7 parts of steel slag powder and 1.2-1.9 parts of sodium silicate.
6. The method for repairing a locally severely corroded steel plate according to claim 1, characterized in that: The raw materials of the water-based EAU wear-resistant and anti-corrosion topcoat include a composite emulsion, a curing component and a reinforcing powder; In parts by weight, the composite emulsion includes 80-100 parts of aqueous EAU composite resin emulsion; The curing component includes 11-14 parts of curing agent, 0.2-0.4 parts of wetting agent, 0.2-0.4 parts of dispersant, 0.2-0.5 parts of defoaming agent, 0.5-0.8 parts of film-forming aid, 0.2-0.4 parts of leveling agent, 5-8 parts of water-based color paste and 25-32 parts of water; The reinforcing powder comprises 2.5-5.5 parts of silicon carbide and 3-7 parts of nano silicon dioxide.
7. The method for repairing a locally severely corroded steel plate according to any one of claims 3 to 6, characterized in that: The curing agent is any one of a water-based polyurea resin and a polyisocyanate curing agent or a combination of the two.
8. The method for repairing a locally severely corroded steel plate according to claim 1, characterized in that: The area to be repaired is an area extending 10-50 cm in all directions along the edge of the damaged part.
9. The method for repairing a locally severely corroded steel plate according to claim 1, characterized in that: The thickness of the non-woven fabric reinforced high barrier layer is 0.5-1 mm, and the thickness of the fiber grid reinforced bearing layer is 3-5 mm.
Citation Information
Patent Citations
Water-based epoxy zinc-rich primer
CN101104771A
Anticorrosion construction technology and method for steel structure
CN107282388A
Metal roof water leakage repairing system
CN108868190A
Water-based environment-friendly single-component waterproof coating and preparation method thereof
CN110157260A
Metal storage tank inner wall anti-corrosion construction process
CN111099190A